Pengembangan Media Pembelajaran Lift The Flap Book Tangga Nada Materi Seni Musik Kelas V SDN Jatirejo Jombang Tahun 2024 - Lestari, Nurma Dwi; Susilo, Claudya Zahrani; Asmarani, Ratih (IJPSE Indonesian Journal of Primary Science Education, 2024)
This research was motivated by a lack of understanding regarding the musical scales of students at SDN Jatirejo Jombang. The aim of this research is to describe the development of media that can foster students' understanding and enthusiasm. This research uses the borg and gall development model. There are 10 stages in the development process that have been implemented in the research. The development phase will be implemented from January 22 to January 31. The media assessment was carried out by material experts, media experts, educators and fifth grade students at SDN Jatirejo Jombang. The results of media development research show that the percentage obtained from the material validator is 87.5% in the category of very valid and suitable for use without improvement, the value obtained from the media validator is 77.94% in the category of very valid and suitable for use without improvement. Furthermore, the results of the educator trial were 87.96% with the category very valid and suitable for use without improvement. The results of the field trial were carried out with 15 students with a percentage of 87.55% in the very interesting category. Based on the results of the overall data analysis, it can be concluded that the development of learning media is suitable for use as learning media.